FINANCIAL TECHNOLOGIES AS A FACTOR IN THE INNOVATIVE DEVELOPMENT OF THE BANKING SYSTEM - Hlushko, Alina; Khudolii, Yuliia (European Science, 2025)
This paper explores the impact of financial technologies (FinTech) on the development of the Ukrainian banking system in the context of economic digitalization. It analyzes the reduction in the number of bank branches from 2019 to 2023 as a result of the